Application of an Adapted Version of MT3DMS for Modeling Back‐Diffusion Remediation Timeframes. Issue 4 (15th September 2015) - Carey, Grant R.; Chapman, Steven W.; Parker, Beth L.; McGregor, Rick
Abstract : Simulation of back‐diffusion remediation timeframe for thin silt/clay layers, or when contaminant degradation is occurring, typically requires the use of a numerical model. Given the centimeter‐scale vertical grid spacing required to represent diffusion‐dominated transport, simulation of back‐diffusion in a 3‐D model may be computationally prohibitive. Use of a local 1‐D model domain approach for simulating back‐diffusion is demonstrated to have advantages but is limited to only some applications. Incorporation of a local domain approach for simulating back‐diffusion in a new model, In Situ Remediation‐MT3DMS (ISR‐MT3DMS) is validated based on a benchmark with MT3DMS and comparisons with a highly discretized finite difference numerical model. The approach used to estimate the vertical hydrodynamic dispersion coefficient is shown to have a significant influence on the simulated flux into and out of silt/clay layers in early time periods. Previously documented back‐diffusion at a Florida site is modeled for the purpose of evaluating the sensitivity of the back‐diffusion controlled remediation timeframe to various site characteristics. A base case simulation with a clay lens having a thickness of 0.2 m and a length of 100 m indicates that even after 99.96 percent aqueous TCE removal from the clay lens, the down‐gradient concentrations still exceed the MCL in groundwater monitoring wells. This shows that partial mass reduction from a NAPL source zone via in situ treatment may have little benefit for the long‐term management of contaminated sites, given that back‐diffusion will sustain a groundwater plume for a long period of time. Back‐diffusion model input parameters that have the greatest influence on remediation timeframe and thus may warrant more attention during field investigations, include the thickness of silt/clay lenses, retardation coefficient representing sorbed mass in silt/clay, and the groundwater velocity in adjacent higher permeability zones. Therefore, pump‐and‐treat systems implemented for the purpose of providing containment may have an additional benefit of reducing back‐diffusion remediation timeframe due to enhanced transverse advective fluxes at the sand/clay interface. Remediation timeframes are also moderately sensitive to the length of the silt/clay layers and transverse vertical dispersivity, but are less sensitive to degradation rates within silt/clay, contaminant solubility, contact time, tortuosity coefficient, and monitoring well‐screen length for the scenarios examined. ©2015 Wiley Periodicals, Inc.